Entry mode strategy in global marketing - Hollensen, Svend (Henry Stewart Talks, 2009)
The entry mode is the institutional/organizational arrangement necessary for entry of a company's product or service into a foreign market, The company's choice of its entry mode is the net result of several, often conflicting forces, The need to anticipate the strength and direction of these forces makes the entry mode decision a complex process with numerous trade-offs between alternative entry modes
Reviewed at 2016/07/31